Wincenty Granat, Panie, szukam Twego oblicza, red. Halina Irena Szumił, Lublin 2008, ss. 408. - Jackiewicz, Małgorzata (Teologia w Polsce, 2020)
Recenzja książki: Wincenty Granat, Panie, szukam Twego oblicza, red. Halina Irena Szumił, Lublin 2008, ss. 408.